Avaliação do network calculus e VCC na caracterização de vídeo MPEG para sistemas multimídia - Fergutz, Laurinei (2010)
The MPEG video coding standard has algorithms for analyzing temporal and spatial video’s redundancies. Therefore, a great variation of data rate is observed in a video sequence. Consequently, planning, design and utilization of the necessary resources for playing video is not an easy task in multimedia systems. This work evaluates the application of Network Calculus (NC) and Variability Characterization Curve (VCC) approaches in MPEG video characterization by providing useful information to setup multimedia systems. Usually, NC theory is applied to obtain performance bounds for packet networks while VCC provides techniques to obtain lower and upper performance bounds for a computational system. However in this work, both NC and VCC are applied to define performance limits expressed as parameters to be used in this work to evaluate resource savings. In addition, a new method is proposed by adding information to the set of parameters used for video characterization. For evaluating these methods in several conditions, a set of tests in accomplished in different configurations with videos MPEG-2, MPEG-4 and H264/AVC. The result is a set of parameters that can be used to characterize videos and point out particularities and requirements imposed by each video to multimedia systems. Finally, a computational tool for evaluating this characterization is also proposed and implemented.